Nanoparticle anchoring targets immune agonists to tumors enabling anti-cancer immunity without systemic toxicity - Yuan Zhang (Nature Portfolio, 2018)
Immunostimulatory agents used in cancer treatment often elicit serious toxicities, limiting their clinical application. Here, the authors show that the use of liposomes to intravenously deliver surface-anchored IL-2 and anti-CD137 proteins enables anti-cancer immunity and reduces the toxic side effects.